Evaluating Validity Evidence for USMLE Step 2 Clinical Skills Data Gathering and Data Interpretation Scores: Does Performance Predict History-Taking and Physical Examination Ratings for First-Year Internal Medicine Residents?. (January 2016) - Cuddy, Monica M.; Winward, Marcia L.; Johnston, Mary M.; Lipner, Rebecca S.; Clauser, Brian E.
Abstract : Purpose: To add to the small body of validity research addressing whether scores from performance assessments of clinical skills are related to performance in supervised patient settings, the authors examined relationships between United States Medical Licensing Examination (USMLE) Step 2 Clinical Skills (CS) data gathering and data interpretation scores and subsequent performance in history taking and physical examination in internal medicine residency training. Method: The sample included 6, 306 examinees from 238 internal medicine residency programs who completed Step 2 CS for the first time in 2005 and whose performance ratings from their first year of residency training were available. Hierarchical linear modeling techniques were used to examine the relationships among Step 2 CS data gathering and data interpretation scores and history-taking and physical examination ratings. Results: Step 2 CS data interpretation scores were positively related to both history-taking and physical examination ratings. Step 2 CS data gathering scores were not related to either history-taking or physical examination ratings after other USMLE scores were taken into account. Conclusions: Step 2 CS data interpretation scores provide useful information for predicting subsequent performance in history taking and physical examination in supervised practice and thus provide validity evidence for their intended use as an indication of readiness to enter supervised practice. The results show that there is less evidence to support the usefulness of Step 2 CS data gathering scores. This study provides important information for practitioners interested in Step 2 CS specifically or in performance assessments of medical students' clinical skills more generally.